NICHO CLIMÁTICO COMO MODELADOR DO PADRÃO DE DISTRIBUIÇÃO DAS ESPÉCIES ARBÓREAS “FRIAS” NA REGIÃO DA BACIA DO PRATA - TOMAZINI, Rita Cassiana Molmelstet,; RIVABEN, Rodrigo Cyrino,; CARDINAL, Renan Henrique Silvestre,; AZEVEDO, Evelyn Mayara Silva,; PONTARA, Vanessa,; BUENO, Marcelo Leandro, (ANAIS DO ENIC, 2025)
-